2009
DOI: 10.1021/ic900699h
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant-Assisted Hydrothermal Synthesis of Eu3+-Doped White Light Hydroxyl Sodium Yttrium Tungstate Microspheres and Their Conversion to NaY(WO4)2

Abstract: In this work, large-scale three-dimensional "flake-ball" microarchitectures of Eu(3+) doped white light hydroxyl sodium yttrium tungstate were prepared by the well-known hydrothermal approach at 180 degrees C for 48 h in the presence of triblock-copolymer poly(ethylene glycol)-block-poly(propylene glycol)-block-poly(ethylene glycol) (P123). NaY(WO(4))(2):Eu(3+) phosphor was formed by annealing the hydrothermal product at approximately 630 degrees C for 2 h. A time-dependent microstructure evolution study was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
47
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(49 citation statements)
references
References 45 publications
2
47
0
Order By: Relevance
“…On the basis of the above results, it is clear that the blue emission of WO 4 2− groups and red emission of the doped Eu 3+ occur simultaneously and yield a white light emission. Such mechanism of the formation of the white light of the as-prepared precursor is consistent with the NaY(WO 4 ) 2 :Eu 3+ precursor reported by Zheng and Lei [22,25]. The corresponding CIE coordinates (x = 0.317, y = 0.267) for the emission spectrum of as-prepared Eu 3+ doped precursor locate in the white light region (point a, Fig.…”
Section: Luminescence Propertiessupporting
confidence: 87%
See 2 more Smart Citations
“…On the basis of the above results, it is clear that the blue emission of WO 4 2− groups and red emission of the doped Eu 3+ occur simultaneously and yield a white light emission. Such mechanism of the formation of the white light of the as-prepared precursor is consistent with the NaY(WO 4 ) 2 :Eu 3+ precursor reported by Zheng and Lei [22,25]. The corresponding CIE coordinates (x = 0.317, y = 0.267) for the emission spectrum of as-prepared Eu 3+ doped precursor locate in the white light region (point a, Fig.…”
Section: Luminescence Propertiessupporting
confidence: 87%
“…As shown, the excitation spectrum of the precursor (Fig. 6A, left) monitored with 615 nm consists of a strong and broad band from 200 to 300 nm with a maximum at about 237 nm, which corresponds to the charge transfer absorption from the 2p orbitals of the oxygen ligands to the 5d orbitals of the central tungsten atoms in the WO 4 2− groups [22,25]. In the longer wavelength region, some weak peaks ascribed to the f-f transitions of the Eu 3+ ions can also be observed.…”
Section: Luminescence Propertiesmentioning
confidence: 83%
See 1 more Smart Citation
“…Tungstates are well-known classical self-activated luminescence materials, which can effectively absorb ultraviolet (UV) and X-ray, then simultaneously migrate the absorbed energy to the doped rare-earth ions through energy transfer, and give their characteristic emissions. Therefore, they are recently considered as promising host materials for rare-earth luminescent centers because of the special properties of WO 4 2-& Guixia Liu liuguixia22@163.com group [11][12][13][14]. From the report of Huang et al [15], it was seen that tungstate host essentially showed a little weaker blue emission at room temperature compared to the absorption in excitation spectrum, owing to efficient energy transfer from WO 4 2-group to activators.…”
Section: Introductionmentioning
confidence: 99%
“…In consideration of this problem, the hydrothermal method is preferred because the synthesis conditions such as temperature and reaction time can be easily adjusted. Furthermore, the hydrothermal process has proved to be a facile and fast route with low cost and energy consumption, which has been widely employed for the synthesis of inorganic materials including alkali rare earth tungstates [11,12,[28][29][30]. Among the alkali rare earth tungstates, the NaY(WO 4 ) 2 lattice belongs to the scheelite CaWO 4 structures, which consists of two formula units in the unit cell, with space group C 4h 6 (I41/a).…”
Section: Introductionmentioning
confidence: 99%